Corporate Governance Memoderasi Pengaruh Manajemen Laba Riil terhadap Nilai Perusahaan - Vanny Talasania; Nelvirita Nelvirita (Universitas Negeri Padang, 2023)
This study aims to examine the effect of real earnings management moderated by corporate governance with five indicators, namely managerial ownership, independent commissioners, institutional ownership, audit committee and leverage on firm value. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique in this study used purposive sampling method, obtained 72 samples in the study from 217 companies from 2018-2021. The data used in this study are secondary data obtained from the company's annual financial statements published by the Indonesia Stock Exchange (IDX) and can be accessed through the website www.idx.co.id. The analysis method used is the SEM-PLS test method using SmartPLS software version 4.0. The results showed that real earnings management has a negative and significant effect on firm value and corporate governance does not weaken the effect of real earnings management on firm value.